Transcranial Direct-Current Stimulation May Improve Discourse Production in Healthy Older Adults - Matar, Shereen J.; Sorinola, Isaac O.; Newton, Caroline; Pavlou, Marousa (Frontiers in Neurology, 2020)
Background: The use of transcranial direct-current stimulation (tDCS) for therapeutic and neurorehabilitation purposes has become increasingly popular in recent years. Previous research has found that anodal tDCS may enhance naming ability and verbal fluency in healthy participants. However, the effect of tDCS on more functional, higher level language skills such as discourse production has yet to be understood. Aims: The present study aimed to investigate in healthy, older adults a) the effect of anodal tDCS on discourse production versus sham stimulation and b) optimal electrode placement for tDCS to target language improvement at the discourse level. Methods: Fourteen healthy, older right-handed participants took part in this sham controlled, repeated measures pilot study. Each participant experienced three different experimental conditions; anodal tDCS on the left inferior frontal gyrus (IFG), anodal tDCS on the right IFG and sham stimulation while performing a story telling task. Significant changes in language performance before and after each condition were examined in three discourse production tasks: recount, procedural and narrative. Results: Left and right IFG conditions showed a greater number of significant within-group improvements (p<0.05) in discourse production compared to sham with 6/12 for left IFG, 4/12 for right IFG and 2/12 for sham. There were no significant differences noted between tDCS conditions. No relationship was noted between language performance and physical activity, age or gender. Conclusions: This study suggests that anodal tDCS may significantly improve discourse production in healthy, older adults. In line with previous tDCS language studies, the left IFG is highlighted as an optimal stimulation site for the modulation of language in healthy speakers. The findings support further exploration of tDCS as a rehabilitative tool for higher-level language skills in persons with aphasia.